Kepraktisan Media APKOBAR dalam Strategi Bioedutainment pada Pembelajaran IPA Sekolah Dasar - Sutariyah Sutariyah; Sumarno Sumarno; Iin Purnamasari (Jurnal Kualita Pendidikan, 2022)
The results of observations and interviews in science learning for fifth grade elementary school, the material of human blood circulation and its functions have difficulty understanding because the teacher is active but the students are passive, and also the limitations of the learning media used by teacher. This study aims to determine the practicality of APKOBAR media in bioedutainment strategies in science learning for students at SDN Tembok 02, Limpung District, Batang Regency. This research is research and development by adopting the ADDIE model (analyze, design, development, implementation, and evaluation). The analyze stage includes initial analysis, student analysis, concept analysis and formulating learning objectives. The design stage includes making the apron media framework, which is designed to have a box-shaped space covered in transparent plastic which is used as a place for material images. The development stage includes combining the collected materials into media and developing instrument data. The implementation phase includes the application of APKOBAR media that has been developed for fifth grade students at SDN Tembok 02. The tests carried out at this stage are product feasibility tests, readability, and pretest-posttest for fifth grade students, with the result showing the readability of small-scale with an average score of 37,5 at interval X > 33,54 with very good category. The students’s readability test on a wide scale obtained an average score of 36,2 at interval X > 33,54 with a very good category. The results of the practicality test by practitioners consisting of class teachers and colleagues were declared valid in terms of appearance, material aspects and language aspects, as evidenced by the acquisition of an average score of 57 with an interval of X > 50.4 with a very good category. The evaluation stage includes the form of evaluation carried out at each stage of the ADDIE model. The conclusion of the study shows that the APKOBAR media in the developed bioedutainment strategy is feasible and practical to use in science learning for elementary school students.